Layanan informasi untuk meningkatkan penyesuaian diri siswa - Risnawati Risnawati; Salahuddin Salahuddin (Orien: Cakrawala Ilmiah Mahasiswa, 2022)
self-adjustment is an ability that students need to have in the transition period. Sometimes there are still students who have not been able to adjust themselves optimally. One of the efforts that can be provided is through information services. The purpose of this study was to determine whether information services were able to improve students' self-adjustment. This research is an experimental type of quantitative research with a one group pretest-posttest control group design. The population in this study was class VIIC MTsNegeri 2 Palu totaling 34 students. All students were used as research samples. To measure the level of adjustment of students used adjustment scale. Data were analyzed through descriptive and inferential statistics. The results showed that information services were able to improve students' self-adjustment